2019
DOI: 10.1080/02640414.2019.1574250
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inspiratory muscle fatigue on acid-base status and performance during race-paced middle-distance swimming

Abstract: The effect of inspiratory muscle fatigue on acid-base status and performance during race-paced middle-distance swimming Inspiratory muscle fatigue, swimming and acid-base status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Interestingly, PImax did not fall further over the course of the 15 tumble turns in the TURNS-IMF trial ( Figure 1 ). Consequently, the overall magnitude of IMF following both 400FC and TURNS-IMF was similar ( Figure 2 ), which is consistent with past studies ( Lomax et al, 2014 ; Lomax et al, 2019 ). Nevertheless, pre-inducing IMF prolonged rotation times and shortened both apnea and swim-out times in comparison to TURNS-C condition ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, PImax did not fall further over the course of the 15 tumble turns in the TURNS-IMF trial ( Figure 1 ). Consequently, the overall magnitude of IMF following both 400FC and TURNS-IMF was similar ( Figure 2 ), which is consistent with past studies ( Lomax et al, 2014 ; Lomax et al, 2019 ). Nevertheless, pre-inducing IMF prolonged rotation times and shortened both apnea and swim-out times in comparison to TURNS-C condition ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…This loading regime has been shown to result in a fall in PImax of 17%–25% in swimmers ( Lomax and Castle, 2011 ; Lomax et al, 2014 ), which is consistent with the magnitude (8%–29%) observed following 100-m and 400-m FC swimming ( Lomax and McConnell, 2003 ; Jakovljevic and McConnell, 2009 ; Thomaidis et al, 2009 ; Brown and Kilding, 2011 ; Lomax et al, 2013 ). Due to hyperventilation arising from the increase in breathing depth, mild hypocapnia and alkalosis may develop as result of the IMF protocol ( Lomax et al, 2019 ). Results of previous studies show that about 1–2 min are required to return breathing pattern and Pco 2 to resting values after the cessation of hyperventilation ( Tawadrous and Eldridge, 1974 ; Meah and Gardner, 1994 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was verified in our study. As the turn includes surface and underwater phases, and accounted by nearly 37% of the total race time, it can be suggested that fatigue not only affect the clean swim but also the turn (Lomax et al, 2019). Indeed, the 5 m-in and 15 m-out (surface phase) did increase along the race.…”
Section: Turnmentioning
confidence: 99%
“…Indeed, swimmers are submitted to inspiratory muscle fatigue while swimming which might induce a deficit in their energetics (Hellard et al, 2010;Lomax et al, 2019). On the other hand, it was shown that an increase in the race distance (between 100 m and 400 m freestyle), did not significantly influenced the degree of inspiratory muscle fatigue (Brown & Kilding, 2011).…”
Section: Turnmentioning
confidence: 99%